PENGGUNAAN MODEL EKONOMETRIKA UNTUK MENENTUKAN INSENTIF PERPAJAKAN BAGI INVESTOR DAN PENGARUHNYA BAGI INVESTASI - ariyanto, sanusi (Balance : Jurnal Akuntansi dan Bisnis, 2024)
This research aims to determine the effect of tax incentives for investors to invest their capital in Indonesia and calculate how many tax incentives can be given to investors. Methodology, The method used is a literature review using multiple linear analysis econometric models. Meanwhile, to test the correlation between incentives and investment in the textile sector in 2020-2021. Results, the of multiple econometric model calculations with existing data, the tax incentive amount is 73.7, with an unpredictable random error (?). Meanwhile, from the correlation test, it was found that tax incentives do not affect investment in the textile industry sector.